Inhibitory effect of (pro)renin receptor decoy inhibitor PRO20 on endoplasmic reticulum stress during cardiac remodeling - Zhang, Jing; Cheng, Yun-Jiu; Luo, Chang-Jun; Yu, Jia (Frontiers in Pharmacology, 2022)
Background: Ectopic activation of renin-angiotensin-system contributes to cardiovascular and renal diseases. (Pro)renin receptor (PRR) binds to renin and prorenin, participating in the progression of nephrology. However, whether PRR could be considered as a therapeutic target for cardiac remodeling and heart failure remains unknown. Materials and Methods: Transverse aortic constriction (TAC) surgery was performed to establish a mouse model of chronic pressure overload-induced cardiac remodeling. Neonatal rat cardiomyocytes (CMs) and cardiac fibroblasts (CFs) were isolated and stimulated by Angiotensin II (Ang II). PRR decoy inhibitor PRO20 was synthesized and used to evaluate its effect on cardiac remodeling. Results: Soluble PRR and PRR were significantly upregulated in TAC-induced cardiac remodeling and Ang II-treated CMs and CFs. Results of In vivo experiments showed that suppression of PRR by PRO20 significantly retarded cardiac remodeling and heart failure indicated by morphological and echocardiographic analyses. In vitro experiments, PRO20 inhibited CM hypertrophy, and also alleviated CF activation, proliferation and extracellular matrix synthesis. Mechanically, PRO20 enhanced intracellular cAMP levels, but not affected cGMP levels in CMs and CFs. Moreover, treatment of PRO20 in CFs markedly attenuated the production of reactive oxygen species and phosphorylation of IRE1 and PERK, two well-identified markers of endoplasmic reticulum (ER) stress. Accordingly, administration of PRO20 reversed ER stressor thapsigargin-induced CM hypertrophy and CF activation/migration. Conclusions: Taken together, these findings suggest that inhibition of PRR by PRO20 attenuates cardiac remodeling through increasing cAMP levels and reducing ER stress in both CMs and CFs.